Penerapan Audit Lingkungan Dalam Menilai Efektivitas Pengelolaan Limbah Rumah Sakit di Rumah Sakit Gotong Royong Surabaya - Boniface Ata Donatus; Ida Bagus Ketut Bayangkara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Hospitals that provide health services also produce waste which will have negative impacts if not managed properly. Hospitals have a responsibility to the environment in conducting their business. Medical waste originating from health service facilities needs appropriate handling based on applicable regulations. This research was conducted to see how the Gotong Royong Hospital manages the waste it produces based on the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning Implementing Regulations of Government Regulation Number 66 of 2014 concerning Environmental Health.This research uses a qualitative method with a case study approach and collects primary data from the environmental health section of the Gotong Royong Hospital, Surabaya. Data analysis and processing methods use technical triangulation, reduction, data display, and drawing conclusions.Based on research, waste management at the Gotong Royong Hospital has been carried out in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023.